The Ludwigsburg-Lucerne Bibliography on Conceptual Change Research in the Geosciences – A Project to Establish a Comprehensive Collection of International Research Papers in the Field - Reinfried, Sibylle; Schuler, Stephan (Journal of Geography Education, 2009)
This paper is a report about the compilation and structure of the Ludwigsburg-Lucerne bibliography on research about alternative conceptions in geography and the geosciences. The bibliography is of great importance because research on students and teachers conceptual frameworks in geography and the geosciences is attracting more and more attention in geography education. Although the research area concerning alternative conceptions has been flourishing in science education in the last 30 years it has not been very prominent in geography until recently. The bibliography documents publications on conceptual frameworks and conceptual change in the geosciences and is work in progress. It is a valuable source of information that facilitates the accessibility to the relevant research papers. Until March 2008 the authors compiled 317 references concerning empirical investigations and theoretical considerations about students' and teachers' conceptual frameworks and conceptual change as well as research on teaching and learning related to conceptual change in the geosciences. The publications were categorized according to the terminology related to the concept of the nested geosphere (e.g. lithosphere, pedosphere, hydrosphere, atmosphere) and sub-categorized using keywords typical for geoscience phenomena of the distinct spheres. The quantification of the number of references in each geoscience field considered helped to get an overview of what has been achieved so far in conceptual change research in the geosciences and revealed research deficits to be tackled in the future. The bibliography can be downloaded at www.ph-ludwigsburg.de/geographie.